2007
DOI: 10.1007/s00606-006-0507-9
|View full text |Cite
|
Sign up to set email alerts
|

Pollination of the European food-deceptive Traunsteinera globosa (Orchidaceae): the importance of nectar-producing neighbouring plants

Abstract: European food-deceptive orchids generally flower early in spring and rely on naı¨ve pollinators for their reproduction. Some species however, flower later in the summer, when many other rewarding plants species are also in bloom. In dense flowering communities, deceptive orchids may suffer from competition for pollinator resources, or might alternatively benefit from higher community attractiveness. We investigated the pollination strategy of the deceptive species Traunsteinera globosa, and more specifically w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
49
0
1

Year Published

2008
2008
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 55 publications
(50 citation statements)
references
References 34 publications
0
49
0
1
Order By: Relevance
“…Several studies have recorded that animal-pollinated plants, especially those pollinated by insects, may have higher visitation rates when co-occurring in communities with species that attract pollinators (Thomson 1978;Feinsinger 1987;Feldman et al 2004;Moeller 2004). This has been recorded as beneficial to non-rewarding species growing in the same plant community and close to individual species that offer a reward (Laverty 1992;Johnson et al 2003a, Juillet et al 2007). Few studies have demonstrated the intra-inter-or multi-species interactions of facilitation for pollinator attraction and flower pollination (Feldman et al 2004;Moeller 2004;Hegland and Totland 2005).…”
Section: Introductionmentioning
confidence: 92%
See 3 more Smart Citations
“…Several studies have recorded that animal-pollinated plants, especially those pollinated by insects, may have higher visitation rates when co-occurring in communities with species that attract pollinators (Thomson 1978;Feinsinger 1987;Feldman et al 2004;Moeller 2004). This has been recorded as beneficial to non-rewarding species growing in the same plant community and close to individual species that offer a reward (Laverty 1992;Johnson et al 2003a, Juillet et al 2007). Few studies have demonstrated the intra-inter-or multi-species interactions of facilitation for pollinator attraction and flower pollination (Feldman et al 2004;Moeller 2004;Hegland and Totland 2005).…”
Section: Introductionmentioning
confidence: 92%
“…Pollination by facilitation is an amazing phenomenon that has been gaining the attention of ecologists who want to understand how the pollination mechanisms between reward and rewardless species work (Johnson et al 2003a;Jersáková et al 2006;Juillet et al 2007). Several studies have recorded that animal-pollinated plants, especially those pollinated by insects, may have higher visitation rates when co-occurring in communities with species that attract pollinators (Thomson 1978;Feinsinger 1987;Feldman et al 2004;Moeller 2004).…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Mostly competitive (Chittka and Schürkens 2001;Brown et al 2002;Bell et al 2005;Totland et al 2006) but also facilitative (Schemske 1981;Moeller 2004) eVects have been found among pollenand/or nectar-rewarding plant species. A special case of facilitation is the "magnet-species eVect," where nonrewarding plant species pollinated by deceit receive more visits when they grow close to attractive plant species than when they grow alone (Laverty 1992;Johnson et al 2003;Juillet et al 2007). A high density of heterospeciWc Xowers can aVect pollination negatively through improper pollen transfer, which occurs when pollinators switch between species (Galen and Gregory 1989;Caruso and Alfaro 2000;Jakobsson et al 2007).…”
Section: Introductionmentioning
confidence: 98%